Dakwah Kultural Muhammadiyah Dalam Menghadapi Generasi Digital Native - Alfarizi, Ahmad Faroch Alfarizi (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
Cultural da'wah is one of the priority programs of the Muhammadiyah Central Leadership for the 2022-2027 period. The targets of cultural da'wah certainly start from the top leadership to the grassroots. The focus of this research is the digital native generation which is very adaptive to technology and certainly needs to be touched by Muhammadiyah's cultural da'wah. This research uses thelibrary research method. The results of this study explain that Muhammadiyah through its cultural da'wah remains purifying, but does not close its eyes to art and culture. In addition to appreciating art and culture, Muhammadiyah also optimizes da'wah through social media in order to touch the digital native generation. This is evidenced by the content presented adjusting and relevant to the needs of digital natives. The success of Muhammadiyah's cultural da'wah to digital natives leaves a mission to create young Muhammadiyah preachers, so that they can realize cultural da'wah through digital natives for other digital natives.